Right to freedom of speech, from freedom to right: is the Malaysian judiciary ready to raise the standard? / Ahmad Suman - Suman, Ahmad (Faculty of Administrative Science and Policy Studies, 2012)
The aim of this paper is to look into the judicial approach adopted by the Malaysian courts in interpreting the constitutional provisions in respect of the right to freedom of speech and expression. Judicial approach is legal principles within which a judge finds support to his reasoning in formulating his decision, and it may vary over a series of periods. The courts could play an important role by adopting a proper approach in tandem with established theories and principles on human rights in order to realise a real and meaningful protection to freedom of speech in its fullest extent. Are the Malaysian courts ready and up to the task? This paper will focus on the aspect of freedom of speech and inevitably it will deal with the basic concepts and theories and the state of affairs of the right in Malaysia. The first part provides the constitutional background in order to provide the framework for the discussion. The second part deals with some previous studies related to the title. Thirdly, the paper will contemplate on the various judicial approaches that the Malaysian courts may consider to actualize a real protection to the right. The paper hopes to reveal that the adoption of appropriate judicial approach to political speech may suggest solutions that lead to a more meaningful protection of the right. The materials in the paper may also assist to a greater extent in charting the direction and prospect of protection to different type of speech against the various competing interests.